Dracula - Spinner, Stephanie; Stoker, Bram, 1847-1912.; Spence, Jim (New York, NY : Random House, 1982)
Having discovered the double identity of the wealthy Transylvanian nobleman, Count Dracula, a small group of people vow to rid the world of the evil vampire.
Keywords: Dracula, Count (Fictitious character) -- Juvenile fiction; Vampires -- Juvenile fiction; Vampires -- Fiction; Horror stories; Transylvania (Romania) -- Juvenile fiction; Horror tales; Psychological fiction